(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In this paper we present the contemporary system of units with their thematic classification and consider its analytical properties in scientific and applied areas. Based on international standards, such as International Système (SI) of Units, this study categorizes units by disciplines and context of use. It demonstrates the interdisciplinary nature of units of measurement in science, engineering, economics, and linguists. The findings support a systematic framework for clinical categorization that can promote scientifically rigorous, cross-geographic research and standardization.